Chemical control of the thermal decomposition temperature of multinary hydrides and complex hydrides - Edwards, P; Grochala, W; Johnson, SR; Kuznetsov, V; Jones, M (2005)
Hydrogen storage is regarded as the scientific and technological barrier inhibiting a transition to a hydrogen energy economy - certainly for the large scale utilization of PEM fuel cells in cars. The maximum hydrogen capacity of conventional (heavy) metal hydrides currently remains at around 2 wt %, which is inadequate for onboard storage of hydrogen which requires a target gravimetric storage density of ≤ 6.5 wt %. Simple atomic, mass-based calculations reveal that the main backbone of any efficient hydrogen storage material must only be built from targeted chemical elements from a short list, Li, Be, B, C, N, O, F, Na, Mg, Al, Si, and P. Due to the toxicities and/or unfavorable chemical properties of hydrogen's compounds with Be, F, Si, and P, the effective list of chemical cogwheels constituting a Hydrogen Storage Material might only consist of only eight elemental apostles. A developing program centered upon an understanding of the thermal decomposition/sorption processes of multinary and complex hydride materials, with a particular emphasis on the rational control and chemical tuning of the strategically important thermal decomposition temperature of compounds and materials from the Light Periodic Table is presented. This is an abstract of a paper presented at the ACS Fuel Chemistry Meeting (Washington, DC Fall 2005).